Design, Dignity and Due Process: The Construction of the Coffs Harbour Courthouse. (June 2018) - Rowden, Emma; Jones, Diane
The discourse around the merit of public architecture often depicts the architect as having complete autonomy over its design. This belies the constraints placed upon creative solutions by design briefs or the intense negotiations between the State, the architect and the various stakeholders involved in the construction process. Through a case study examining the construction of a courthouse, we demonstrate the difficulties in pursuing improvements to the phenomenological experience of justice within these constraints. It reveals the need for architectural knowledge to be shared for the common good in order to resist practices that replicate existing conditions and inhibit innovation.